Global Quality of Life Among WHI Women Aged 80 Years and Older - Naughton, Michelle J. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND. The number of older adults living to age 80 and older is increasing rapidly, particularly among women. Correlates of quality of life (QOL) in very advanced ages are not known. We examined the association of demographic, social-psychological, lifestyle, and physical health variables with global QOL in a Women’s Health Initiative (WHI) cohort of women aged 80 and older. METHODS. 26,299 WHI participants, who had completed a recent psychosocial and medical update, were included in these analyses. Global QOL was assessed by a single item, asking the women to rate their overall QOL on a scale from 0 to 10. Characteristics of the women were examined by the level of their transformed global QOL scores (≤50, 50–70, ≥70), and multiple regression was used to examine which demographic, social-psychological, lifestyle and health variables were independently associated with higher global QOL. RESULTS. Social-psychological and current health variables were more strongly associated with global QOL than a history of selected comorbid conditions. In particular, higher self-rated health and fewer depressive symptoms were the most strongly associated with better global QOL in WHI women ≥80 years. CONCLUSIONS. Interventions to reduce depressive symptoms and improve health may lead to better self-reported health and global QOL among older women. Physical and mental health screenings followed by evidence-based interventions are imperative in geriatric care.